2023
DOI: 10.3389/fpsyg.2023.1122277
|View full text |Cite|
|
Sign up to set email alerts
|

Learning digital skills online: empowering older adults through one-to-one, online digital training provision

Gemma Wilson-Menzfeld,
Jessica Raven Gates,
Mary Moreland
et al.

Abstract: IntroductionDigital exclusion, through lack of access and poor digital skills, can have an adverse impact on daily living. Not only did the COVID-19 pandemic dramatically impact the necessity of technology in our daily lives, but also reduced the availability of digital skills programmes. This study aimed to explore perceived facilitators and barriers of a digital skills programme that was delivered remotely (online) and to reflect on this form of training as a possible alternative to traditional face-to-face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Additionally, whichever dimension is considered, the results of the analysis support the need for strategies adapted to the specific needs and preferences of older individuals. Recent scientific studies also underscore the necessity for an individual and customized approach to acquire relevant digital skills for the elderly [101], promoting at the same time the idea of flexible solutions in view of specific needs and challenges, such as fears, a lack of previous experience, or possible physical limitations [102]. At the same time, the importance of social support is emphasized, considering the process of ensuring the successful implementation of digital skills development programs among the elderly [102].…”
Section: Summative Overview Of Cultural Disparitiesmentioning
confidence: 99%
“…Additionally, whichever dimension is considered, the results of the analysis support the need for strategies adapted to the specific needs and preferences of older individuals. Recent scientific studies also underscore the necessity for an individual and customized approach to acquire relevant digital skills for the elderly [101], promoting at the same time the idea of flexible solutions in view of specific needs and challenges, such as fears, a lack of previous experience, or possible physical limitations [102]. At the same time, the importance of social support is emphasized, considering the process of ensuring the successful implementation of digital skills development programs among the elderly [102].…”
Section: Summative Overview Of Cultural Disparitiesmentioning
confidence: 99%
“…To date, the majority of digital literacy programs have been focused on increasing technology acceptance, adoption, use, or interest, with some success [16][17][18][19][20][21]. As technology has the potential to help older adults stay connected to friends and family, many technology-based interventions have been focused on reducing loneliness, but these have had mixed results, often attributed to failure to target socially isolated older adults [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As technology has the potential to help older adults stay connected to friends and family, many technology-based interventions have been focused on reducing loneliness, but these have had mixed results, often attributed to failure to target socially isolated older adults [22][23][24][25]. Studies have reported that social support to set up new devices plays an important role in initiating and motivating tablet use among older adults [18] and that consideration of older adults' needs, preferences, and lived experience is essential to success [17,19]. Indeed, a recent systematic review of instructional strategies to promote the learning of digital technology among older adults reported that collaborative, personalized, relevant, and experience-based learning strategies accompanied by repetition and effective teaching aids (such as print resources) were themes present throughout many of the 17 studies reviewed [26].…”
Section: Introductionmentioning
confidence: 99%